Dermatovenereologic health care delivery management in the Russian Federation. Results of 2018 - A. A. Kubanov; E. V. Bogdanova (State Scientific Center of Dermatovenereology and Cosmetology, 2019)
The paper presents the analysis of resources and the results of work of dermatovenereologic healthcare organizations in 2018. The dynamics of incidence of sexually transmitted infections, and the dynamics of prevalence of skin disorders in the Russian Federation is described.